Does Acquisition Improve Financial Performance? Evidence from Public Companies in Indonesia - Cean Maria Bella; M. Shalahuddin; Henny Oktaviyani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Mergers and acquisitions (M&A) activity in Indonesia has continued to increase and is theoretically expected to generate synergies—such as cost efficiency, strengthened market share, and diversification—thereby improving corporate financial performance. However, empirical evidence is often inconsistent and suggests that the benefits of acquisitions are not always immediately reflected in post-transaction performance. This study employs a quantitative approach with a comparative design to examine differences in financial performance before and after acquisitions among 10 publicly listed companies that conducted acquisitions in 2021, using an observation period of one year prior to the acquisition (2020) and three years after the acquisition (2022–2024). Performance is measured using ROA, ROE, DER, Current Ratio (CR), and EPS. The analysis is conducted using the Wilcoxon Signed Rank Test. The results show no significant differences between pre-acquisition and post-acquisition financial performance across all variables for the 2022–2024 period. These findings indicate that acquisitions have not been proven to improve profitability, liquidity, capital structure, or shareholder value in the short to medium term. Therefore, acquisition success is likely determined more by the effectiveness of post-acquisition integration, integration cost control, and the quality of synergy strategy implementation than by the acquisition decision alone.